POTENTIAL LOSS OF PBB-P2 REVENUE AS REGIONAL TAX IN SAMBAS REGENCY - Yarlina Yacoub; Safari Safari; Nindya Lestari (AFEBI Economic and Finance Review, 2018)
This study aims to identify the potential loss in the receipt of Rural and Urban Land and Building Taxes (PBB-P2) as Regional Taxes in Sambas Regency. This research uses descriptive method by describing events in the field using survey methods and questionnaires which will then be processed using the SWOT method. The data used in this study consisted of two data.Based on the results of interviews on questionnaires given to sample taxpayers to find out the reasons and factors that caused taxpayers to take tax evasion actions, it was found that there were the taxpayers  do not know / do not understand, not very important about PBB-P2. In an effort to minimize the level of potential loss various efforts made by the government at that time both those that have been carried out and those that will be carried out in the future. There are several relevant strategies to be implemented in an effort to optimize PBB-P2 revenues as local taxes in Sambas Regency, among others: Utilizing regional autonomy policies to implement regional regulations more firmly (law enforcement); Repairing and completing facilities and infrastructure facilities to support regional revenue management, especially supporting facilities for increasing PBB-P2 revenues; Providing incentives for PBB-P2 collection so that officers get additional motivation in an effort to optimize PBB-P2 revenues; Utilizing the willingness and awareness of taxpayers to pay taxes in order to increase PBB-P2 revenues by implementing programs and activities well and orderly. Responding to the enactment of Law No. 28 of 2009 with initiative and creativity in the management of PBB-P2 which in the end was able to increase regional Original Revenue (PAD) towards regional financial independence.JEL Classification: H20, H21, H24Keywords: Fiscal, Potential Loss, Revenue